Strengths-based prevention : reducing violence and other public health problems - Banyard, Victoria L.; Hamby, Sherry L. (American Psychological Association, 2022)
"A new way of thinking about prevention that focuses on building assets and resources This book provides practitioners and researchers with the means to make more impactful choices in the design and implementation of prevention programs. Drawing from state-of-the-art research on a range of behavior problems such as violence, drug abuse, suicide, and risky sexual activity, Victoria Banyard and Sherry Hamby present a strengths-based approach to prevention. Historically, most prevention efforts have focused too much on admonishment and knowledge transfer, despite years of evidence that such programs are ineffective. Effective prevention must be grounded in a broad understanding of what works, what does not, and how different forms of risky behavior share common elements. This book synthesizes research on behavior change from a variety of disciplines, including psychology, public health, sociology, criminology, resilience science, critical race theory, and even urban planning. It emphasizes the importance of building enough protective strengths to insulate people from risks"--